Evolution of the schools of first letters and its impulse by Carlos III. Special reference to the Regulation for the establishment of free schools for girls of 1783 - Anguita Osuna, José Enrique (2019)
The configuration of education as a right and value in today's society is related to the creation and development of primary schools during the Ancient Régime, which were originally reserved for the privileged classes. The approaches of enlightened intellectuals allowed public authorities to detect the need to improve elementary education, and to create more and better schools of the so called "first letters", even for the most popular classes. This policy became one of the main educational objectives of Carlos III, who also opted to encourage the presence of girls in schools of first letters through the adoption of the Regulation for the establishment of free schools for girls in 1783.